Perceived inhibitors to rural practice among physiotherapy students - R. A. Mitchell (AOSIS, 1997)
This descriptive study was undertaken to determine perceptions of undergraduate physiotherapy students which would make them more or less likely to enter rural practice. A total of 607 self-administered questionnaires were distributed to undergraduates in The University of Sydney and 546 completed documents were returned. Students perceived the major inhibitors as social (isolation from family, friends and partner) and recreational (lack of theatre, entertainment, etc). Influences which would attract graduates to rural practice were lifestyle (relaxed, less stressful, healthier), lower cost of living, seeing more of Australia and professional autonomy. Knowledge of these perceptions will enable educators, the profession and potential employers to develop and implement strategies that will negate the negative and re-enforce the positive perceptions.